2010
DOI: 10.1016/j.neuroimage.2010.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cognitive control of response inhibition by the anterior cingulate cortex in autism spectrum disorders

Abstract: Response inhibition, or the suppression of prepotent, but contextually inappropriate behaviors, is essential to adaptive, flexible responding. In autism spectrum disorders (ASD), difficulty inhibiting prepotent behaviors may contribute to restricted, repetitive behavior (RRB). Individuals with ASD consistently show deficient response inhibition while performing antisaccades, which require one to inhibit the prepotent response of looking towards a suddenly appearing stimulus (i.e., a prosaccade), and to substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
155
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(178 citation statements)
references
References 113 publications
(156 reference statements)
23
155
0
Order By: Relevance
“…This network is thought to integrate bottom-up attention and top-down executive control to mediate interactions between other large-scale networks, such as the FPTCN and DMN, and to assign value to stimuli for later processing (45). The nodes of the SN have been implicated in disparate tasks ranging from social processing (46)(47)(48) to purely cognitive tasks (49). Intra-SN connections and SN-DMN connections were highly predictive of change in ABAS general adaptive composite (GAC) score (r 2 > 0.3)-a domain-general measure of adaptive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This network is thought to integrate bottom-up attention and top-down executive control to mediate interactions between other large-scale networks, such as the FPTCN and DMN, and to assign value to stimuli for later processing (45). The nodes of the SN have been implicated in disparate tasks ranging from social processing (46)(47)(48) to purely cognitive tasks (49). Intra-SN connections and SN-DMN connections were highly predictive of change in ABAS general adaptive composite (GAC) score (r 2 > 0.3)-a domain-general measure of adaptive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Primary nodes of the salience network are the anterior cingulate cortex and anterior insula, which neuroimaging studies suggest have a role in perception of social exclusion (Bolling et al, 2011;Masten et al, 2011) and cognitive control (Agam et al, 2010). A recent study ) compared connectivity in large-scale brain networks in children with ASD and matched controls.…”
Section: Boxmentioning
confidence: 99%
“…During the past few years, a number of studies suggested that ADHD might be caused by a neurotransmitter system impairment (Nikolas et al 2010;Roman et al 2004) that explains a resulting loss of brain activation during RI. The dysfunction of some key neural circuits for RI could lead to apparent disinhibition of behaviors in the context of fast-changing environments (Agam et al 2010), which might provide a better understanding of RI deficits in ADHD. Neuroimaging studies which identified abnormalities in the key brain pathways of RI (Martin et al 2006;Mostofsky and Simmonds 2008) could extend our present knowledge of ADHD, and particularly functional magnetic resonance imaging (fMRI) has the unique power to reveal aberrant brain activity without hurting the human body (Smith et al 2006;Suskauer et al 2008;Tamm et al 2004;Vaidya et al 2005).…”
Section: Introductionmentioning
confidence: 99%